THE STUDENT PERCEPTIONS, ITEM ANALYSIS, AND ISLAMIC ACADEMIC PERFORMANCE IN THE REPRODUCTION BLOCK AT THE FACULTY OF MEDICINE UMP - Nabil Gusapo Rynando; Titik Kusumawinakhyu; Yunia Annisa (International Islamic Medicine Forum, 2025)
The Faculty of Medicine at Universitas Muhammadiyah Purwokerto (FK UMP) integrates Islamic values into its curriculum, particularly within the reproduction block, aligning with national and Muhammadiyah competency standards. Student performance in Islamic materials is assessed using multiple-choice questions (MCQs), which are analyzed for quality. This study examines the correlation between student perceptions, item analysis, and Islamic academic performance in the reproduction block at FK UMP. An observational, analytic, cross-sectional study was conducted among 103 FK UMP students (class of 2021). Data were collected via a validated 35-item perception questionnaire (Cronbach’s alpha = 0.86) and MCQ item analysis using Anates version 4.0. Scores on 10 Islamic MCQs measured academic performance. The results show that there is no significant correlation found between student perceptions and academic performance (p = 0.278). However, item analysis significantly correlated with academic performance (p < 0.01). The conclusion of this research is that student perceptions did not significantly impact academic performance; high-quality MCQ items were strongly associated with better Islamic academic outcomes in the reproduction block. ABSTRAK Fakultas Kedokteran Universitas Muhammadiyah Purwokerto (FK UMP) mengintegrasikan nilai-nilai Islam ke dalam kurikulumnya, terutama dalam blok reproduksi, yang selaras dengan standar kompetensi nasional dan Muhammadiyah. Kinerja mahasiswa dalam materi keislaman dinilai dengan menggunakan pertanyaan pilihan ganda (MCQ), yang kemudian dianalisis kualitasnya. Penelitian ini menguji korelasi antara persepsi mahasiswa, analisis butir soal, dan kinerja akademik Islam di blok reproduksi di FK UMP. Penelitian observasional, analitik, dan cross-sectional dilakukan pada 103 mahasiswa FK UMP (angkatan 2021). Data dikumpulkan melalui kuesioner persepsi 35 item yang telah divalidasi (Cronbach's alpha = 0,86) dan analisis item MCQ menggunakan Anates versi 4.0. Skor pada 10 MCQ Islam mengukur kinerja akademik. Hasil penelitian menunjukkan bahwa tidak ada korelasi yang signifikan antara persepsi siswa dan kinerja akademik (p = 0,278). Namun, analisis butir soal berkorelasi secara signifikan dengan prestasi akademik (p <0,01). Kesimpulan dari penelitian ini adalah bahwa persepsi mahasiswa tidak secara signifikan berdampak pada kinerja akademik; item MCQ berkualitas tinggi sangat terkait dengan hasil akademik Islam yang lebih baik di blok reproduksi.